Identifying the optimal flexural performance of metal-composite single-lap joints with copolyester-reinforced epoxy adhesive under various loading rates using the Grey Relation Analysis - Erbayrak, Engin; Erbayrak, Seda; Eker, Beril; Colak, Murat (ELSEVIER SCI LTD, 2026)
This study examines the best flexural performance of metal composite single-lap joints fabricated with copolyester-reinforced epoxy adhesives at various loading rates using the Grey Relation Analysis (GRA). The study consists of three parts. The first part involves the formation of metal composite single-lap joints and their experimental approach under different loading rates. In the experimental approach, A356 aluminum was used as the metal material with the addition of titanium (Ti) and boron (B) additives. Plain-woven glass fiber-reinforced epoxy (GFRE) and plain-woven carbon fiber-reinforced epoxy (CFRE) were served as the composite materials. The lap joints were tested in three-point bending tests under loading rates of 1, 10, and 50 mm/min, respectively. In the second part, a numerical analysis was conducted using boundary conditions similar to the experimental conditions. In the numerical analysis, a 6-node pentahedral cohesive element was utilized, representing a novel approach for modeling adhesives in finite element analysis (FEA). When experimental and numerical results were compared, a difference of 4.36% was observed between the maximum load values and 6.80% between the failure displacements. Based on these results, it can be said that the experimental results converge with the numerical results. In the last part of the study, performance rankings of metal composite joints were determined using the Grey Relational Analysis (GRA) method, which enabled us to identify the optimum joint. This systematic approach facilitated the scientific design of joints that demonstrate optimal flexural performance under various loading conditions.
Keywords: Metal-composite single-lap joints; 6-Node pentahedral cohesive element; Grey relation analysis; Flexural test; STRENGTH; TEMPERATURE; TENSILE; Engineering; Materials Science